AMBIENT SONG KARYA KELOMPOK MUSIK DINDING KOTA KAJIAN TENTANG PROSES PEMBUATAN DAN PEMANFAATAN SEBAGAI MEDIA MEDITASI (Jurnal Seni Musik, 2016)
Meditation is a step to know yourself for the good and balance life. It’s can be helped with used music for media called ambient music. In Semarang there is a musical group that plays ambient music named Dinding Kota. The purpose of this study to describe how to create an ambient that can be used as a medium meditation which has benefited as information for the public to know the ambient function. This research uses qualitative descriptive method with data collection in the form of interview, observation, and documentation. In making the ambient group has nine steps Dinding Kota in the form of contempatation, choose a background, choose themes and concept, choose an instrument, select pedal effect, set the pedal effect, set amplifier, and make ambientpart and ambient notes. The use of ambient as a medium of meditation done using headphone or a headset with a body sitting cross legged posisition or lying down and focus on listening to ambient music. Ambient is a type of music which resulted in another dimension there that may effect one’s thoughts and suggestios with the sound echoing hum’s that can be used as a medium of meditation.